General aggregation of misspecified asset pricing models - Nikolaj Gospodinov; Esfandiar Maasoumi (Federal Reserve Bank of Atlanta, 2017)
This paper proposes an entropy-based approach for aggregating information from misspecified asset pricing models. The statistical paradigm is shifted away from parameter estimation of an optimally selected model to stochastic optimization based on a risk function of aggregation across models. The proposed method relaxes the perfect substitutability of the candidate models, which is implicitly embedded in the linear pooling procedures, and ensures that the aggregation weights are selected with a proper (Hellinger) distance measure that satisfies the triangle inequality. The empirical results illustrate the robustness and the pricing ability of the aggregation approach to stochastic discount factor models.
Keywords: C13; C52; G12; 330; entropy; model aggregation; asset pricing; misspecified models; oracle inequality; Hellinger distance